Choice of optimal biocide combination to control flies (Diptera: Muscidae) - Mihaela Kavran; Marija F Zgomba; Aleksandra M Ignjatovic-Ćupina; Sanja D Lazić; Dušan V Petrić (Annals of Agricultural and Environmental Medicine, 2015)
Introduction Introduction. Flies – by feeding on decaying matter, human waste and food – have been implicated in the spread of numerous animal and human diseases. Excessive fly populations are generally associated with livestock units and domestic waste due to decaying organic matter. A large number of flies cause extreme disturbance in the behavior of the host, resulting in skin irritation, lesions, wounds, and secondary infections are likely to appear.